Metal Allergy and Systemic Contact Dermatitis: An Overview - Yoko Yoshihisa; Tadamichi Shimizu (Hindawi Limited, 2012)
Contact dermatitis is produced by external skin exposure to an allergen, but sometimes a systemically administered allergen may reach the skin and remain concentrated there with the aid of the circulatory system, leading to the production of systemic contact dermatitis (SCD). Metals such as nickel, cobalt, chromium, and zinc are ubiquitous in our environment. Metal allergy may result in allergic contact dermatitis and also SCD. Systemic reactions, such as hand dermatitis or generalized eczematous reactions, can occur due to dietary nickel or cobalt ingestion. Zinc-containing dental fillings can induce oral lichen planus, palmoplantar pustulosis, and maculopapular rash. A diagnosis of sensitivity to metal is established by epicutaneous patch testing and oral metal challenge with metals such as nickel, cobalt, chromium, and zinc. In vitro tests, such as the lymphocyte stimulating test (LST), have some advantages over patch testing to diagnose allergic contact dermatitis. Additionally, the determination of the production of several cytokines by primary peripheral blood mononuclear cell cultures is a potentially promising in vitro method for the discrimination of metal allergies, including SCD, as compared with the LST.